Terpolymerization of polyethylene glycol maleate with acrylamide and monovinyl ether of monoethanolamine - Burkeyeva, G.K. (KSU Publ., 2017)
Radical copolymerization of polyethylene glycol maleate with acrylamide and monovinyl ether of monoethanol amine has been performed for the first time. Radical co- and terpolymerization of the systems polyethylene glycol maleate with acrylamide and monovinyl ether of monoethanol amine has been studied. Molecular weight of polyethylene glycol maleate has been determined using light scattering and gel permeation chromatography. The compositions of the polymers and copolymerization constants of the studied systems have been determined. The composition of the copolymers has been found using gas chromatography. Kinetic curves show that with increasing molar fraction of acrylamide in the solution the reaction rate and swelling capacity of the copolymers increase. It has been shown that the composition of terpolymers determined experimentally differs considerably from the one calculated taking into account obtained constants of copolymerization. Deviations found are due to various intermolecular interactions in these systems. The possibility of controlling the properties of network copolymers of polyethylene glycol maleate by changing external factors has been studied. Swelling capacity of the copolymers investigated was studied using gravimetric method.
Полиэтиленгликольмалеинаттың акриламидпен жəне моноэтаноламиннің моновинилді эфирімен терполимеризациясы
Терполимеризация полиэтиленгликольмалеината с акриламидом и моновиниловым эфиром моноэтаноламина
Keywords: unsaturated polyesters; copolymerization; terpolymerization; polyethylene glycol maleate; acrylamide; copolymer; terpolymer